EFFECTS OF Azadirachta indica, Parkia biglobosa AND SYNTHETIC INSECTICIDES ON Sesamia calamistis (HAMPSON) ON GROWTH AND YIELD OF MAIZE (Zea Mays L.) IN MAKURDI (FUDMA JOURNAL OF SCIENCES, 2024)
Zea mays, plays a crucial role in the dietary habits of numerous individuals residing in Nigeria. Several factors, including the presence of Sesamia calmistis and the effects of synthetic insecticides on beneficial insects and hazards to humans, contribute to the limitation of maize output. The study evaluated the effect of Azadirachta indica and Parkia biglobosa extracts on the control of S. calamistis and this experiment was carried out in two planting seasons of 2021 and 2022. The experiment was carried out at the Teaching and Research Farm, Joseph Sarwuan Tarka University, Makurdi. Three treatments; A. indica, P. biglobosa, Karate 5 EC (Lambda cyhalothrin 5 EC) and control were used. From the study, A. indica extract had a significant effect at p
Keywords: Botanical; Azadirachta indica; Parkia biglobosa; Extracts; Karate 5 EC